AFPC representative farm economic outlook for the 2025 FAPRI Baseline - Joe L. Outlaw; Bart L. Fischer; George M. Knapek; J. Marc Raulston; Brian K. Herbst; Henry L. Bryant; Henry R. Nelson; Natalie A. Graff (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2025)
The farm-level economic impacts of the FAPRI 2025 Baseline on representative crop and livestock operations are projected in this report, assuming provisions of the 2018 Farm Bill are in effect and continue throughout the 2025-2030 projection period. The current representative farm analysis output reflects an evaluation of ARC/PLC program elections for the farms given provisions of the 2018 Farm Bill. Producers are assumed to enroll in the program resulting in the highest ending cash reserves at the end of the projection period; as farm update meetings are conducted, adjustments, if necessary, are made to program elections. The analysis was conducted using a whole farm simulation model developed by AFPC with necessary data sourced from: Producer panel cooperation to develop economic information to describe and simulate representative crop, livestock, and dairy farms, and Projected prices, policy variables, and input inflation rates from the Food and Agricultural Policy Research Institute (FAPRI) 2025 Baseline. The simulations incorporate historical risk faced by farmers for prices and production. This report presents the results of the baseline in a risk context using selected simulated probabilities and ranges for annual financial measures. The probability of a farm experiencing negative ending cash reserves and the probability of a farm losing real net worth are included as indicators of the cash flow and equity risks facing farms through the year 2030.
Keywords: 330